DNA Topoisomerase 1 Structure-BASED Design, Synthesis, Activity Evaluation and Molecular Simulations Study of New 7-Amide Camptothecin Derivatives Against Spodoptera frugiperda - Jiang, Zhiyan; Zhang, Zhijun; Cui, Gaofeng; Sun, Zhipeng; Song, Gaopeng; Liu, Yingqian; Zhong, Guohua (Frontiers in Chemistry, 2018)
Camptothecin and its derivatives (CPTs) have strong toxicity to eukaryotic cells by targeting their DNA topoisomerase 1 (Top1) protein and have been increasingly explored as potential pesticides for plant protection. However, the detailed structure-binding mechanism of the interactions between CPTs and the insect Top1 protein remains unclear, which significantly hinders the development of novel CPTs as new insecticides. Herein, a series of 7-amide camptothecin analogues based on the binding mode of camptothecin in complex with Top1 (SfTop1)-DNA from Spodoptera frugiperda cultured cell line Sf9 were designed and synthesized. Fifteen of these compounds exhibited excellent cytotoxic activity (values of IC50 from 2.01 to 6.78 μM) compared with camptothecin (29.47 μM). The docking studies revealed the binding mechanism when the camptothecin parent rings were inserting parallel to DNA bases and stabling the ternary complex by π–π stacked and hydrogen-bond interactions, and further suggested that introduction of lipophilic and some electron-withdrawing groups on the amide linkage of camptothecin could be beneficial to its activity via some non-covalent interactions. Furthermore, almost all the synthesized compounds could inhibit the growth of Spodoptera litura larvae strongly (Inhibition rate from 50.20% to 79.05%), superior or comparable to camptothecin (55.69%) after 8 days of exposure. In particular, the compounds 4c, 4d, 4f, and 4j, which presented more than 70% inhibitory activities, were deserved to be developed as potential biorational pesticides. The information described here would be useful for the further design and development of potentially effective pesticides in the field of plant protection.